Environmental Injuries: Hyperthermia and hypothermia - McDonald, A.; Stubbs, R.; Lartey, P.; Kokot, S. (MacEwan University Student eJournal, 2020)
Environmental injuries are an important type of sport injury to study as they can occur year-round, through a variety of activities, and occur to a broad range of athletic populations. Hyperthermia (a core body temperature above 38.5°C) and hypothermia (a core body temperature below 35°C) are two common environmental injuries that can be life threatening. This research paper examines the mechanisms of how and why these injuries occur and the effect they have on the body. This paper also outlines preventative measures to take, including identifying internal and external predisposing risk factors, as well as ways to treat hyperthermia and hypothermia to return an athlete back to play.